HUBUNGAN KEJELASAN PENULISAN DIAGNOSIS DAN KELENGKAPAN PENGISIAN RESUME MEDIS DENGAN KETEPATAN KODE DIAGNOSIS DI BANGSAL PENYAKIT DALAM DI RUMAH SAKIT X - Maisharoh, Maisharoh; Sari, Dian; Gusmita, Dini (Ensiklopedia of Journal, 2024)
The accuracy of the diagnosis code is the suitability of the diagnosis code determined by the coding officer with the patient's medical record in accordance with ICD-10 rules. The results of the observations showed that one of the problems was that 60% of doctors' writing was difficult for staff to read and 55% of patients' medical record resumes were still incomplete. The aim of this research was to find a relationship between the clarity of writing a diagnosis and the completeness of filling out a medical resume with the accuracy of the diagnosis code in the internal medicine ward of Hospital X in the city of Padang. The type of research used is quantitative with analytical descriptive methods. The population is all medical resumes of inpatients in the internal medicine ward, a sample of 96 medical resumes using saturated sampling techniques. The research was carried out by observation using the bivariate analysis technique chi-square test. Research results from observations showed that 56 (58.3%) wrote unclear diagnoses, 66 (66.6%) filled in incomplete medical resumes and 35 (36.4%) incorrect diagnosis codes, and. There is no significant relationship between the clarity of writing a diagnosis and the accuracy of the diagnosis code and there is no significant relationship between the completeness of filling out a medical resume and the accuracy of the diagnosis code. It is hoped that in the future officers will confirm again with the medical personnel concerned if there is an illegible writing of the diagnosis and incomplete filling in so that there are no errors in assigning the diagnosis code.